The casual ethnography of the executive suite - Westney, D Eleanor; Van Maanen, John (Journal of International Business Studies, 2011)
Some of the most influential work in international business (IB) is grounded by what looks remarkably like ethnographic fieldwork, in which researchers hang out with the executives of the companies they study and incorporate into their analysis the insights they gain. Valuable as this work is, it often fails to reflect on how these sources have shaped the account, and it projects the subculture of the executive suite onto the entire organization. IB would benefit from complementary “serious” ethnography that is reflective about sources, builds on the rich ethnographic research literature, and focuses on how the managed struggle to make sense of the directives from the executive suite.